Philosophy as a vanitas: Lyotard’s exploded Sublime (Itinera, 2021)
French philosopher Jean-François Lyotard’s changing concepts of the sublime (after Immanuel Kant) are traced here. Overriding normative responses to Lyotard’s Artforum texts on the sublime of the later 1980s, I argue for a fulcrum moment shared with painter Jacques Monory in California in the later 1970s, and the collision of astronomy, the digitalisation of data, the microprocessor and neuroscience. Lyotard’s exhibition Les Immatériaux (Pompidou Centre, 1985) exemplified interdisciplinarity at the parameters of knowledge, shunning postmodern irony. Lessons on the Analytic of the Sublime: Kant’s Critique of Judgement, §§ 23–29, (1991, English 1994), a resumé of Lyotard’s courses, stands in perpetual tension with his art world engagement. The genre of the vanitas in art and its long time-axis challenges classical philosophy — likewise a genre and set of procedures. Might not philosophy also confront its own ‘death’ or epistemological obsolesence? A coda takes Lyotard’s ‘techno-sublime’ into the era of bitcoin.
Keywords: Lyotard, sublime, digital, vanitas